Liberating Methodologies and Nakba Studies: Palestinian History and Memory from below as Sites of Lifelong Learning. Issue 1 (May 2014) - Masalha, Nur
<x xml:space="preserve">Abstract</x> Historians too often construct frameworks and methodologies which obfuscate social, economic and political oppression. This article explores new historical methodologies that can represent oppressed and marginalised groups in Palestine. In particular the article focuses on the role of indigenous history and memory in critical learning and shaping individual and collective identity in Palestine. It further argues that Palestinian memories 'from below' since the Nakba have played a major positive role in the recovery from the traumatic catastrophe and the reconstruction of Palestinian identity. The article critiques the manipulation of collective memory by social, political and economic elites and top-down nationalist approaches. It argues that reconfigured popular memories can be liberating and empowering for embattled Palestinians. The article also calls for the establishment of an interdisciplinary subfield of Nakba Studies that would bring together historians, social memory and cultural theorists, postcolonial scholars and scholars of trauma studies with the aim of documenting and studying the embattled social memory of Palestine as a site of lifelong learning and empowerment.